Multistage artificial immune system (MAIS) for voltage stability network reconfiguration in distribution system / Muhammad Azhar Ismail - Ismail, Muhammad Azhar (2013)
This paper presents the optimization technique for optimal network reconfiguration approach. Optimal Network Reconfiguration in power system is obtained by configuring the ON/OFF status of sectionalizing and tie-line switches. Multistage AIS optimization technique will be used to find the network reconfiguration with voltage stability improvement and loss minimization as the objective function. This approach is believed to provide an efficient way to control the tie-line and sectionalizing switches.